2010
DOI: 10.1186/1471-2180-10-44
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the outer membrane proteome of Salmonella enterica serovar Typhimurium utilising a lipid-based protein immobilization technique

Abstract: BackgroundSalmonella enterica serovar Typhimurium (S. Typhimurium) is a major cause of human gastroenteritis worldwide. The outer membrane proteins expressed by S. Typhimurium mediate the process of adhesion and internalisation within the intestinal epithelium of the host thus influencing the progression of disease. Since the outer membrane proteins are surface-exposed, they provide attractive targets for the development of improved antimicrobial agents and vaccines. Various techniques have been developed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…However, it seemed that it reduced the numbers of soluble OMPs in this study, since it can solubilize inner membrane protein and OMP in SG . Overall, the MW spots of most SG‐OMPs were distributed between 10–15 kDa and 30–45 kDa, and the results corresponded with theoretical data that previously showed that OMPs in Salmonella species were located at 36, 38, 42, and 45 kDa . In addition, all the spots of SG‐OMPs were in the range of 4–8 p I and the most of them were detected in the range of 4.0–5.5 p I .…”
Section: Resultssupporting
confidence: 86%
“…However, it seemed that it reduced the numbers of soluble OMPs in this study, since it can solubilize inner membrane protein and OMP in SG . Overall, the MW spots of most SG‐OMPs were distributed between 10–15 kDa and 30–45 kDa, and the results corresponded with theoretical data that previously showed that OMPs in Salmonella species were located at 36, 38, 42, and 45 kDa . In addition, all the spots of SG‐OMPs were in the range of 4–8 p I and the most of them were detected in the range of 4.0–5.5 p I .…”
Section: Resultssupporting
confidence: 86%
“…This suggests that if gene products do facilitate bile acid entry as a requisite for SPI-1 repression, they too are either redundant or essential. The former is especially likely considering the plethora of outer membrane proteins and porins expressed by Salmonella with the potential to permit bile acid entry (56,57). This is supported by the finding that exposure of Salmonella to deoxycholate is accompanied by downregulation of ompD.…”
Section: Discussionmentioning
confidence: 99%
“…Seleim and others (2002) performed preparation of the Salmonella OMPs with 2% sarkosyl in 10 mM HEPES buffer. Chooneea et al (2010) attempted to characterize the surface proteome of S. Typhimurium using lipid-based protein immobilization technology in the form of LPI TM FlowCell. No detergents were required and no sample clean up was needed prior to downstream analysis.…”
Section: The Role Of Ompsmentioning
confidence: 99%